The Use of Deictic Elements in Ælfric’s Catholic Homilies - Inčiuraitė, Lina (Verbum, 2012)
The phenomenon of deixis is still the dominant topic for investigation in the field of pragmatics. The study seeks to analyze distinct types of deictic categories in the medieval world heritage, namely Ælfric’s Catholic Homilies. Deictic expressions are considered to be highly relevant for the research of these homilies as they perform a leading role in the connectivity of sermons. Moreover, incorrect use of deictic elements can give rise to misunderstanding and unsuccessful communication betwixt the speaker and the addressee. The search for deictic expressions which are encoded in pronouns or adverbs in the selection of Ælfric’s Catholic Homilies has been assisted by an excessive use of Benjamin Thorpe’s English translation (1844). The context of sermons lets us determine and decipher the meaning of deictic expressions which change in distinct contexts with the speaker’s position either in time or space. The study uses the framework of deixis proposed by Stephen Levinson (1983) as well as a pragmatic approach for the analysis of distinct types of deictic elements in Ælfric’s Catholic Homilies. The findings of the study reveal that the sermons exhibit various deictic categories, namely person, place, time, and discourse. Moreover, these categories as well as the predication clearly show the proximity or distance of the speaker to the referred object. As far as tense is concerned, it is a temporal deictic device. In Ælfric’s Catholic Homilies, the present tense is the proximal form, whereas the past tense is the distal form.